Assessment of linear anionic polyacrylamide application to irrigation canals for seepage control - Hamil Uribe; Rodrigo Figueroa; Luis Llanos (Journal of Agricultural Engineering, 2013)
South- central area of Chile area has a Mediterranean climate and high crop water requirements. Irrigation water is distributed through long channels which have low water conveyance efficiency (Ec), difficult to improve by conventional techniques. The objective of this study was to quantify Ec and to evaluate the use of Linear Anionic Polyacrylamide (LA-PAM) to reduce seepage losses. The study was carried out in south-central area of Chile, (UTM Coordinate N 5745000; E 725000 m, datum is WGS-84, zone 18S) in 250 km of channels whose flow varied between 0.12 and 24.6 m3 s–1. Water users indicated channel reaches with potential low Ec, which were selected for LA-PAM application. In 11 reaches between 0.51 and 3 km in length, 1 to 3 LAPAM applications were performed at rates of 10 kg ha–1, considering the wet perimeter area as basis of calculation. Thirty-one LA-PAM applications were performed over a 30.5 km length. Most of the channels were large enough to allow motorboat moving against the current to carry-out LA-PAM application. Water flow was measured (StreamPro ADCP) at both ends of selected reaches before and after granular LAPAM application. Weekly measurements were made to quantify treatment effect duration. Water turbidity and temperature were measured. Channels showed variable Ec from 87% to 94%. Two reaches showed 6% water gains. In more than 80% cases LA-PAM effect was positive, achieving loss reductions of 15 to 760 L s–1. In other cases LA-PAM had a negative effect since it mainly affected water entry into the channel. It was determined that field conditions referred by users as indicators of Ec are not always correct and vary in time according to climatic conditions. Ec was estimated and it was possible to reduce seepage through LA-PAM applications. This allow increasing irrigation security in critical periods, especially under drought conditions.